DEVELOPMENT OF PEDAGOGICAL SKILLS OF A FOREIGN LANGUAGE TEACHER THROUGH EDUCATIONAL TECHNOLOGIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The academic discipline “Foreign Language” is of particular importance in the light of the modernization of education. Being an essential element of the culture of the native people of a given language and a means of transmitting it to others, a foreign language contributes to the formation of a holistic picture of the world in students. The main purpose of a foreign language is to develop communicative competence. Mastering a foreign language in the context of the second generation federal state standards involves the use of modern pedagogical technologies by the teacher. The article discusses technologies such as pedagogical workshops and the development of critical thinking in English lessons.